Study on the Stability of Coal Pillars Under the Disturbance of Repeated Mining in a Double-Roadway Layout System - Liu, Shuaigang; Bai, Jianbiao; Wang, Xiangyu; Wang, Guanghui; Wu, Bowen; Li, Yanhui; Zhao, Jiaxin (Frontiers in Earth Science, 2021)
The double-roadway layout system, which is extensively applied in large mines, has the potential to significantly balance excavation-mining and improve mine ventilation and transportation capacity. However, the coal pillar in the double-roadway layout system is easily destabilized due to the disturbance of repeated mining, which has a significant impact on the safety and reliability of coal mines. This paper takes the coal pillar and its supporting structure of the double-roadway layout system as the research object, establishes a UDEC trigon numerical calculation model, and systematically corrects the input parameters, while explaining the excavation method of roadways and the simulation method of the supporting structure element. The numerical simulation results show that under the conventional support intensity conditions, the internal damage of the coal pillar during the excavation period is about 20%, while the internal damage to the coal pillar develops to 55% throughout the first-panel mining. During the disturbance of repeated mining, the damage in the coal pillar increased to 90%, and the coal pillar was already in a state of failure. Under the combined control of rock bolts and counter-pulled anchor cables, the coal pillar damage does not change significantly during the excavation and first-panel mining. During the disturbance of repeated mining, the damage of the coal pillar is reduced to 63%. There is a certain low damage area in the coal pillar, which can ensure the stability of the coal pillar and its supporting structure as a whole. Furthermore, the on-site monitoring results show that the maximum value of the floor-to-roof and rib-to-rib convergence of a W1310 tailgate during the repeated mining disturbance stage is 730 and 620 mm, respectively. The findings of this study give an approach to—as well as estimated values for the design of, including its “small structure” control technical parameters—the double-roadway layout system.